Earthquake Excited Base-Isolated Structures Protected by Tuned Liquid Column Dampers: Design Approach and Experimental Verification. (2017) - Adam, Christoph; Matteo, Alberto Di; Furtmüller, Thomas; Pirrotta, Antonina
Abstract: In this contribution a direct approach for optimal design of a Tuned Liquid Column Damper (TLCD) device attached to the base slab of a base-isolated structure is presented, aiming at reducing the seismic displacement demand of the base-isolation subsystem. Assuming white noise base excitation, for a wide parameter range a direct optimization procedure yields design charts for optimal TLCD quantities. The performance of the base-isolated structure equipped with optimally tuned TLCD device in comparison to the simple base-isolated one is evaluated both numerically and experimentally. In a numerical study the system is subjected to the 44 records of the FEMA P-695 far-field ground motion set. The experimental studies are conducted on a three-story small-scale base-isolated shear frame model. From the results it can be concluded that a TLCD effectively controls the seismic response of earthquake excited low-damped base-isolated structures.